Maximizing Rewards Through Work Infrastructure - Gunawan Nainggolan, Hendra; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2025)
This study aims to analyze the influence of Competence and Work Discipline on Rewards, with Work Infrastructure as a moderating variable at PT PLN (Persero) Rantauprapat Customer Service Implementation Unit. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) as the method of analysis. A total of 86 employees participated as respondents in this study. The results show that Competence (coefficient = 0.388; T-statistic = 3.266; P-value = 0.001) and Work Discipline (coefficient = 0.276; T-statistic = 2.307; P-value = 0.011) have a positive and significant effect on Rewards. Work Infrastructure also has a positive and significant effect on Rewards (coefficient = 0.362; T-statistic = 3.274; P-value = 0.001). However, the moderation analysis revealed that the interaction between Competence and Work Infrastructure (coefficient = -0.031; T-statistic = 0.235; P-value = 0.407) and the interaction between Work Discipline and Work Infrastructure (coefficient = 0.112; T-statistic = 0.900; P-value = 0.184) do not have significant effects on Rewards. Therefore, employee rewards are more directly influenced by competence, discipline, and the availability of work infrastructure, rather than by the moderating role of infrastructure.